The Effect of Shift Work on Fatigue in Processing Workers at PTPN IV Kebun Adolina Serdang Bedagai District - nasution, Nita anggina; Harahap, Reni Agustina (Journal for Quality in Public Health, 2023)
Work fatigue is aconditions experienced by the workforce which can result in a decrease in vitality and work productivity. Fatigue is a state of tiredness associated with working long hours, long periods without sleep, or the requirement to work hours out of sync with the body's biological rhythms. Work fatigue will reduce performance and increase the level of work errors. Increased work errors will provide opportunities for work accidents in the industry, as well as reduce work effectiveness. This study aims to determine the effect of work shifts on fatigue in processing workers at PTPN IV Kebun Adolina, Serdang Bedagai District. This type of research is quantitative with a cross-sectional research design. A total of 70 respondents were sampled by probability sampling. Univariate and bivariate statistical analysis using the chi-square test. The results of the bivariate analysis showed that there was an effect of shift work on fatigue in processing workers. The results of statistical tests using chi-square obtained a p-value of 0.001 <0.05. To overcome this, the company can provide drinks and provide additional nutritious food.